J-matrix calculation of electron-helium S-wave scattering. II. Single ionization and single excitation - Konovalov, D; Fursa, D; Bray, Igor (American Physical Society, 2012)
In the preceding paper [Konovalov et al., Phys. Rev. A 84, 032707 (2011)] we used the J -matrix (JM) method to solve the S-wave e-He scattering problem within the frozen-core model of helium. In the present work we go beyond the frozen-core model and adopt a general configuration-interaction description of helium (within the S-wave model). As a result a more accurate description of the helium target states is achieved that allowed us to obtain highly accurate numerical solutions of the e-He scattering problem for the elastic, 21,3S, 31,3S excitation and total ionization cross sections. The JM results are confirmed by the corresponding convergent-close-coupling (CCC) calculations. At energies above the ionization threshold some minor pseudoresonances are still evident in both the JM and CCC results despite the large bases used. The pseudoresonances are nearly completely eliminated by averaging a number of JM calculations creating a challenging benchmark for any current or future ab initio electron-atom scattering methods.